A WHO key informant language survey of people with lived experiences of diabetes: Media misconceptions, values-based messaging, stigma, framings and communications considerations. (November 2022) - Hunt, Daniel; Lamb, Krista; Elliott, James; Hemmingsen, Bianca; Slama, Slim; Scibilia, Renza; Whitney Daniels, Kristen; Mikkelsen, Bente
Abstract: Aims: This study aimed to learn from people with lived experiences of diabetes to raise the quality of diabetes communications. Methods: An online key informant survey for people (18+) with a direct and/or adjacent (caregiver, friend, family-member etc., ) lived experience of diabetes. Through thematic analysis, we gathered insights on perceptions of media reporting on diabetes and communicating with accuracy, impact and without stigma. Descriptive analysis also investigated effective values for WHO to communicate diabetes with key audiences of policy-makers, funding partners and the general public. Results: 918 respondents in 58 WHO Member States were analysed. Participants identified five key themes requiring more appropriate consideration in the media: accurately defining diabetes types, over-emphasis on sugar and lifestyle, negative impacts of diabetes stigma, burden of costs (financial, personal and interpersonal) and mental health. Irrespective of audience, key values-based messages identified as important for WHO to convey included: 'urgency', 'preventing suffering', 'improving wellbeing' and 'meaningful engagement' of people with lived experience. Conclusion: Learning from people with lived experience of diabetes identifies key diabetes communication considerations. Continued meaningful engagement of this group, including in WHO's work and the multistakeholder diffusion of this methodology to local contexts, could improve public discourse on diabetes and related policies.